Cultivation-dependent and cultivation-independent investigation of O-methylated pollutant-producing bacteria in three drinking water treatment plants. (1st March 2023) - Tang, Yiran; Wu, Zhixuan; Zhang, Yanfen; Wang, Chuanxuan; Ma, Xuelian; Zhang, Kejia; Pan, Renjie; Cao, Yucheng; Zhou, Xinyan
Highlights: Microbial O -methylation of diclofenac is firstly proved in drinking water. A MPN method is established to quantify OMPPB in drinking water. OMPPB risks are assessed in terms of odor, toxicity and bioaccumulation. OMPPB community structure is shifted during drinking water treatment. Mycobacterium and Pelomonas significantly influence the OMPFP profile. Abstract: O -methylated pollutants (OMPs) are emerging contaminants in drinking water and mainly produced through bacterial O -methylation. However, the information of OMP-producing bacteria (OMPPB) in drinking water treatment plant (DWTP) is largely unknown so far. In this study, the OMPPB in water samples from three DWTPs (XL, JX and NX) were investigated by using cultivation-dependent and cultivation-independent technologies. Four OMPs were detected and their odor and toxicity risks were assessed. Formation potentials (FPs) of 2, 4, 6-trichloanisole, 2, 3, 6-trichloanisole, 2, 4, 6-tribromoanisole, pentachloroanisole and diclofenac methyl ester were determined in water samples and their values shifted significantly among DWTPs. A most probable number (MPN) method was established to quantify OMPPB numbers and the relationships between total haloanisole FPs (HAFPs) (y) and OMPPB numbers (x) in three DWTPs could be described by the following functions: y = 0.496× 0.373 (XL), y = 0.041× 0.465 (JX) and y = 0.218× 0.237 (NX). Several genera like Bacillus, Ralstonia, Brevundimonas, etc. were newly found OMPPB among the cultivable bacteria, and their OMP products were evaluated in terms of quantity and environment risks (odor, toxicity and bioaccumulation). High-throughput sequencing revealed treatment process was the main driving factor to shape the OMPPB community structures and Mantel test showed HAFP profile was significantly influenced by Mycobacterium and Pelomonas . PICURSt2 analysis discovered four phenolic O -methyltransferases (OMTs) and four carboxylic OMTs which might be responsible for OMP formation. Several strategies were recommended to assess risk and control contamination brought by OMPPB in DWTPs. Graphical abstract: Image, graphical abstract